Finding of novel polyhydroxybutyrate producer Loktanella sp. SM43 capable of balanced utilization of glucose and xylose from lignocellulosic biomass - Lee, Sun Mi; Cho, Do Hyun; Jung, Hee Ju; Kim, Byungchan; Kim, Su Hyun; Bhatia, Shashi Kant; Gurav, Ranjit; Jeon, Jong Min; Yoon, Jeong Jun; Kim, Wooseong; Choi, Kwon Young; Yang, Yung Hun (International Journal of Biological Macromolecules, 2022)
Polyhydroxybutyrate (PHB) is a potential substitute for plastics derived from fossil fuels, owing to its biodegradable and biocompatible properties. Lignocellulosic biomass could be used to reduce PHB production costs; however, the co-utilization of sugars, such as glucose and xylose, without catabolite repression is a difficult problem to be solved. Here, we selected a novel Loktanella sp. SM43 from a marine environment and optimized the conditions for PHB production. Loktanella sp. SM43 showed high PHB production (66.5% content) from glucose. When glucose and xylose were used together, this strain showed high utilization of both substrates compared to other high PHB-producers such as Halomonas sp. and Cupriavidus necator, which showed glucose preference. Loktanella sp. SM43 showed high growth and PHB production with lignocellulosic hydrolysates. When pine tree hydrolysates were used, PHB production was the highest at 3.66 ± 0.01 g/L, followed by Miscanthus (3.46 ± 0.09 g/L) and barley straw hydrolysate (3.36 ± 0.36 g/L). Overall, these results reveal the potential of Loktanella sp. SM43 to produce PHB using various lignocellulosic hydrolysates as feedstock and the first systematic study for PHB production with Loktanella sp. The approach of screening novel strains is a strategy to overcome co-utilization of sugars without genetic engineering.
Keywords: Biomass; Fermentation; Glucose; Hydroxybutyrates; Lignin; Sugars; Xylose; Lignocellulosic biomass; Loktanella sp.; Polyhydroxybutyrate